THE INTERMEDIATE SPACE - Kangelaris, Fotis (Design/Arts/Culture, 2022)
Starting from the question of why things have a form, we develop the concept of the “Intermediate Space” as a procedure during which the “thing” assumes its form as a word or as a picture. However, this intermediate space can constitute itself its final form. Looking into, in the first place, the concept of the “Intermediate Space” as a basic structural function of psychopathology, we focus, later, on three examples on which we base our aspect. The Garden as the “Intermediate Space” of the countryside-city/nature-civilisation, unconscious-conscious. The Architecture as the “Intermediate Space” between matter and spirit as for its agony to be art. In this unit, after the initial observations, there is a focus on the concepts of “rurbain” and the “ladder”. “Non finito” in art where the route of the “thing” to its form as art crystallizes before its final shaping. Towards this, we look into different appearances of art and we expand on relevant philosophical comments. In the final part of our study, we attempt through questions an elevation of the human’s life to a “Non finito” work. The “thing”, as far as this study is concerned, has to be heard in the concept of the lacanian topology and the freudian “Das Ding”.